Dnevnik XIX vsesoiuznoi konferentsii KPSS . Dnevnik XIX vsesoiuznoi konferentsii KPSS . Diary of the 19th All-Union Conference of the Communist Party of the Soviet Union . Дневник XIX всесоюзной конференции КПСС - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The anchorman's report about the make up of the composition of the Conference's participantsamts and about the course of the conference; discussion of the problem of the election of the Soviets' leadership and of the problem of reforming Soviet press; a journalist's conversation with the delegates of the Congress of Soviets in the hall of the Palace of Soviets. Доклад ведущего о составе участников конференции и о ходе конференции; обсуждение проблемы выборов руководства советов и проблемы реформы советской прессы; беседа журналиста с делегатами Съезда Советов в фойе Дворца Советов.